2012
DOI: 10.1590/s0036-46652012000600002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five methods for oxacillin susceptibility testing of Staphylococcus aureus isolates from cystic fibrosis patients

Abstract: SUMMARYMethicillin-resistant Staphylococcus aureus (MRSA) are now a worldwide problem. Cystic fibrosis (CF) patients are commonly colonized and infected by MRSA. Accurate oxacillin susceptibility testing is mandatory for the adequate management of these patients. We performed a comparison of the accuracy of different tests in CF isolates, including methicillin-susceptible S. aureus and MRSA with different SCCmec types, and using the mecA gene as the gold-standard. The sensitivity and specificity of oxacillin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…7,8 The detection of mecAgene by PCR is considered as the gold standard, but most of the hospitals lacking the advanced laboratory services required for the molecular methods essential for fast and precise identification of methicillin-resistant isolates. 9 These days the cefoxitin disk diffusion test is commonly used in clinical microbiology setups. In the light of rules of the clinical and laboratory standards institute (CLSI), the cefoxitin disk diffusion assay should be used to confirm the mecA-mediated oxacillin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The detection of mecAgene by PCR is considered as the gold standard, but most of the hospitals lacking the advanced laboratory services required for the molecular methods essential for fast and precise identification of methicillin-resistant isolates. 9 These days the cefoxitin disk diffusion test is commonly used in clinical microbiology setups. In the light of rules of the clinical and laboratory standards institute (CLSI), the cefoxitin disk diffusion assay should be used to confirm the mecA-mediated oxacillin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Although mecA polymerase chain reaction seems to be the most accurate method, it is still not available throughout the world due to financial and technical issues. In addition, it does not detect the other rare but possible mechanisms of oxacillin resistance, including other modified penicillin-binding proteins and beta-lactamase overproduction.…”
mentioning
confidence: 99%
“…As we have previously proposed,[23] a more appropriate option for increasing the sensitivity of methicillin resistance detection would be the concomitant use of two phenotypic methods, such as oxacillin and cefoxitin disk diffusion, or oxacillin agar screening plate and cefoxitin disk diffusion. Any isolate resistant by at least one of the tests should be reported as resistant.…”
mentioning
confidence: 99%
“…[1] In this setting, accurate laboratory detection of oxacillin resistance is paramount to ensure appropriate clinical and epidemiological decisions. [23] Although there are recommendations from both the Clinical and Laboratory Standards Institute (CLSI) and the European Committee on Antimicrobial Susceptibility Testing (EUCAST), there is also, still, discussion regarding the method of election for routine use by clinical microbiology laboratories.…”
mentioning
confidence: 99%
“…did not evaluate specifically this method. We have previously studied[23] the accuracy of both oxacillin and cefoxitin disk diffusion tests, oxacillin agar screening plate and Etest™ using the presence of the mecA gene as gold standard, and concluded that, even with the cefoxitin modified breakpoints that were later adopted, there are still major errors with the disk diffusion tests. Etest™ and oxacillin agar plate showed higher accuracy.…”
mentioning
confidence: 99%